2022
DOI: 10.1007/s11629-021-7073-z
|View full text |Cite
|
Sign up to set email alerts
|

Rock temperature variability in high-altitude rockfall-prone areas

Abstract: In a context of cryosphere degradation caused by climate warming, rock temperature is one of the main driving factors of rockfalls that occur on high-elevation mountain slopes. In order to improve the knowledge on this critical relationship, it is necessary to: i) increase measurement capability for rock temperature and its variability in different lithological and slope/aspect conditions; ii) increase local scale studies; iii) increase the quality and the comparability of the observational data. This paper sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
1
5
0
1
Order By: Relevance
“…In addition to glacial retreat, increasing temperature plays an important role in rockfall hazard [21,22,40,[75][76][77][78]. Consistent with trends presented in Section 4.1, guides have observed an increase in temperature and decrease in overnight freezes, which has significantly increased the rockfall hazard on the Ramp: "The rockfall hazard, it's gone from a manageable problem if you get up really early and have a cold night too.…”
Section: (G14)supporting
confidence: 70%
“…In addition to glacial retreat, increasing temperature plays an important role in rockfall hazard [21,22,40,[75][76][77][78]. Consistent with trends presented in Section 4.1, guides have observed an increase in temperature and decrease in overnight freezes, which has significantly increased the rockfall hazard on the Ramp: "The rockfall hazard, it's gone from a manageable problem if you get up really early and have a cold night too.…”
Section: (G14)supporting
confidence: 70%
“…B) The aspect of slopes where movements initiated before 2000 range between NE and S (mainly S and SE), while that of slopes which failed after year 2000 is between SW and E (mainly N). It is well known that slopes facing from E to S are the ones most subject to thermal fluctuations, both on a daily and seasonal scale, being the most exposed to solar radiation (Nigrelli et al, 2022). However, several studies (e.g., Nagai et al, 2013) have shown that high-elevation slopes facing N are the most subject to instability due to permafrost degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Slope aspect is closely related to solar radiation. For instance, south-facing slopes receive intense solar radiation, resulting in signi cant diurnal temperature variations in rock masses and making them susceptible to mechanical weathering (Nigrelli et al 2022). Moreover, increased temperatures lead to increased evaporation, making it di cult for vegetation to grow on south-facing slopes.…”
Section: Factor Analysismentioning
confidence: 99%